2007
DOI: 10.1523/jneurosci.4401-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Anti-GM1 Antibodies Cause Complement-Mediated Disruption of Sodium Channel Clusters in Peripheral Motor Nerve Fibers

Abstract: Voltage-gated Naϩ (Na v ) channels are highly concentrated at nodes of Ranvier in myelinated axons and facilitate rapid action potential conduction. Autoantibodies to gangliosides such as GM1 have been proposed to disrupt nodal Nav channels and lead to Guillain-Barré syndrome, an autoimmune neuropathy characterized by acute limb weakness. To test this hypothesis, we examined the molecular organization of nodes in a disease model caused by immunization with gangliosides. At the acute phase with progressing limb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
281
1
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(298 citation statements)
references
References 63 publications
9
281
1
7
Order By: Relevance
“…In summary, many collaborative efforts have demonstrated that anti-GM1 and anti-GQ1b antibodies bind to peripheral nerve and neuromuscular junctions 64,65 , and anti-GD1a antibodies bind to the nodes of Ranvier, paranodal myelin and neuromuscular junction 66,67,68 . Upon binding, the antibodies activate the complement cascade, resulting in formation of the membrane attack complex, disruption of sodium channel clusters at the node of Ranvier with disruption of nodal architecture 69 , and calcium influx and calpain-dependent neuronal and glial injury at the neuromuscular junction 70,71 .This injury can be ameliorated with complement inhibitors 72,73 .…”
mentioning
confidence: 99%
“…In summary, many collaborative efforts have demonstrated that anti-GM1 and anti-GQ1b antibodies bind to peripheral nerve and neuromuscular junctions 64,65 , and anti-GD1a antibodies bind to the nodes of Ranvier, paranodal myelin and neuromuscular junction 66,67,68 . Upon binding, the antibodies activate the complement cascade, resulting in formation of the membrane attack complex, disruption of sodium channel clusters at the node of Ranvier with disruption of nodal architecture 69 , and calcium influx and calpain-dependent neuronal and glial injury at the neuromuscular junction 70,71 .This injury can be ameliorated with complement inhibitors 72,73 .…”
mentioning
confidence: 99%
“…This "molecular mimicry" theory has been further substantiated by establishing animal models of human GBS. Rabbits sensitized with GM1-like LOS from C. jejuni (CF90-26) generate IgG anti-GM1 Abs that induce complement-mediated disruption of sodium channel clusters in the peripheral nerves, leading to the development of flaccid limb weakness (7). It is noteworthy that, whereas most IgG Abs against bacterial polysaccharides are of the IgG2 isotype, the cross-reactive IgG Abs to gangliosides and LOS that develop during C. jejuni enteritis-associated GBS comprise primarily IgG1 and IgG3 subclasses (8).…”
mentioning
confidence: 99%
“…A comparison of ganglioside location between normal mice and ganglioside synthase knockout mice by co-staining for neuronal markers may be also useful for analyzing the function of affected gangliosides. Furthermore, this approach can detect the localization of gangliosides suspected as target antigens that might be expressed by a certain subpopulation of DRG neurons (Gong et al, 2002) and a subregion at the nodes of Ranvier (Susuki et al, 2007) in autoimmune neuropathies. Co-staining for type IV collagen readily outlines the tissue framework (Matsuno et al, 1996), including the nerve cell body, myelin sheath, and blood vessels, enabling us to locate gangliosides easily.…”
Section: Discussionmentioning
confidence: 99%